Fertility Preservation for Young Women with Breast Cancer: Review and Perspective - Shuxin Zheng; Limei Cai; Zhiming Miao; Yinlong Yang (IMR Press, 2024)
Objectives: Breast cancer is a common malignancy that poses a significant danger to women. Recently the risks of breast cancer have been increasing in younger populations, and treatments may affect the ability to conceive, requiring options for fertility preservation. The clinical management of breast cancer typically involves surgery, chemotherapy, and radiotherapy, all of which may present detrimental effects on fertility. Thus, it is crucial to consider fertility preservation when formulating treatment plans. Mechanism: A narrative review was conducted to analyze the available literature regarding the impact of breast cancer treatment modalities on fertility, as well as strategies for fertility preservation. Findings in Brief: Various breast cancer treatment modalities can result in varying degrees of damage to a patient's ovaries, potentially compromising their ovarian function and subsequently affecting their fertility. This article reviews various fertility preservation methods, including oocyte and embryo cryopreservation, controlled ovarian stimulation (COS), in vitro maturation (IVM), cryopreservation, and ovarian tissue transplantation. Additionally, we discuss several potential strategies, such as 3D bioprinting, Traditional Chinese Medicine (TCM), and Artificial Intelligence (AI) assisted treatment. Conclusions: The impact of breast cancer treatment modalities and fertility preservation strategies exhibits individual variability, necessitating the clinical selection of treatment based on the specific circumstances of each patient. The integration of 3D bioprinting, TCM, and AI is expected to provide a new perspective for young breast cancer patients seeking to maintain their fertility.